Racing against Yourself: High Stakes for Adolescent English Language Learners with Disabilities. Issue 9 (September 2017) - Bondie, Rhonda; Zusho, Akane
Background/Context: Achieving academic readiness is difficult in high-stakes testing environments (HSTEs) and even more challenging for English Language Learners with Learning Disabilities (ELLD). Transforming classroom cultures to emphasize the development of competence and motivationally supportive practices could moderate some of the potentially deleterious effects of a HSTE on ELLD. Purpose/Objective/Research Question/Focus of Study: This qualitative case study explored the impact of All Learners Learning Every Day (ALL-ED)—a mastery-oriented teacher professional development (PD) program—on ELLD's readiness to tackle challenges in HSTEs. Setting: The study was conducted at an international high school in the south Bronx, NY. Participants: Participants included three classroom teachers (one general education English teacher, one general education math teacher, and one special education teacher) and 13 students. Intervention: This study examines the impact of instructional routines (small group discussions and self-regulation) on ELLD in a HSTE. Research Design: A qualitative case study was used to examine the impact of instructional routines in a specific context from multiple perspectives. Data Collection and Analysis: Data were collected throughout the school year including student drawings, student and teacher interviews, and researcher memos. A protocol for analysis and interpretation was used to explore student conceptualization through drawing. Using constant comparison analysis, in-vivo codes were organized into meaningful themes and then sorted into two perspectives of self-reflection called "student experiences" and communication to others called "student advice to teachers." Paralleling the student interviews, in-vivo codes were used to determine key words and phrases for each teacher and common across teachers. Findings/Results: The first research question investigated the impact of HSTE on ELLD's motivation to learn. The following themes emerged; student feelings relate to perception of understanding, classroom conversation and confidence, individual teacher conferences, curriculum clarity (goals, activities, quality), comparisons to other students, and expectations of progress are success. The second research question investigated the impact of ALL-ED routines in HSTE. Five key practices were identified that aided in establishing a mastery-oriented and supportive learning environment. Conclusions/Recommendations: This study elucidates tensions among limited time, the complexity of coordinating effective instructional practices across teacher teams, and spe-cific instructional needs of ELLD in HSTE. Perspectives from the students challenge our understanding of the finish line in the race to acquire language, content knowledge, and skills in school by suggesting that all assessments be placed within a cycle of learning and feedback that together along with many other experiences provide evidence of growth and academic competence.